Trajectory control algorithms for the de-orbiting and Re-entry of the MISTRAL satellite. (February 2023) - Nocerino, A.; Notaro, I.; Morani, G.; Poderico, M.; D'Amato, E.; Blasi, L.; Fedele, A.; Fortezza, R.; Grassi, M.; Mattei, M.
Abstract: This paper presents the trajectory control strategies for the de-orbiting and re-entry phases of a micro satellite equipped with a deployable and controlled aero-brake. They are framed in the design of the Italian space mission MISTRAL (MIcro-SaTellite with Air-Launchable Re-entry capabilities) developed under the supervision of the DAC-Campanian Aerospace District . The proposed control approach makes use of two different control strategies for the de-orbiting and re-entry phases, respectively. The former is based on a linear quadratic optimal control, whereas the latter is based on a model predictive control approach. Numerical simulation results demonstrate the effectiveness of the proposed approach which guarantees a good compromise between stability and performance during the mission phases of interest. Highlights: A control strategy for the de-orbiting and re-entry phase of a micro-satellite using a deployable aero-brake is proposed. An LQR-based approach with state feedback is used for the de-orbiting phase. An MPC approach with a terminal cost on the prediction time horizon is used for the re-entry phase. Performance is assessed numerically by modelling both the entire GNC system and the satellite dynamics. The achieved tracking error is compatible with the required landing accuracy of 250 km.